2018
DOI: 10.1002/cite.201700009
|View full text |Cite
|
Sign up to set email alerts
|

Waste Water Treatment with Reeds in a Mobile Root Space Treatment Plant

Abstract: Für temporäre Einsätze zur Behandlung kommunaler Abwässer wurde eine mobile Wurzelraumkläranlage getestet, deren Reaktionsraum ausschließlich aus Schilfwurzeln als Aufwuchsfläche für Mikroorganismen besteht. Die Anlage wurde in der Vegetationsperiode 2016 mit vorgeklärtem kommunalem Abwasser einer Großkläranlage beschickt. Bei einem Zulaufvolumenstrom von 1200 L d−1 wurden die Ablaufgrenzwerte für den chemischen Sauerstoffbedarf und den biochemischen Sauerstoffbedarf zuverlässig eingehalten. Kurzzeitige Belast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Plants in constructed wetlands can also promote the development of aphids. For example, Zehnsdorf et al [147] observed an increase in the occurrence of aphids-probably the mealy plum aphid (Hyalopterus pruni)-in a constructed wetland planted by reed on a pilot scale in Germany ( Figure 6). This species of aphid seeks out reed as a summer host, while it spends winter on stone fruit trees such as plum or peach trees [148].…”
Section: Impacts Of Constructed Wetlands On Biodiversitymentioning
confidence: 99%
“…Plants in constructed wetlands can also promote the development of aphids. For example, Zehnsdorf et al [147] observed an increase in the occurrence of aphids-probably the mealy plum aphid (Hyalopterus pruni)-in a constructed wetland planted by reed on a pilot scale in Germany ( Figure 6). This species of aphid seeks out reed as a summer host, while it spends winter on stone fruit trees such as plum or peach trees [148].…”
Section: Impacts Of Constructed Wetlands On Biodiversitymentioning
confidence: 99%